(untitled) (Discourse of Law and Administration, 2023)
The present article is aimed to determine the economic relevance of the VAT refund tool for travellers and whether the legal regulations in this area are optimal. The problem specified here has an interdisciplinary character and constitutes an analysis of the relation of travellers’ export to the export of Poland and its selected voivodeships (Podlaskie and Lubelskie Voivodeships) to Belarus in order to determine the significance of the phenomenon examined from an economic and legal perspective. Based on this, the hypothesis was that the mechanism of VAT refunds to travellers brings economic benefits, however, the construction of regulations and practice could be conducive to abuse in this aspect. The methods used to verify the hypothesis were: dogmatic-legal, analysis of literature, regulations and case law, quantitative method, and structured interviews with employees of the National Tax Administration and with entrepreneurs.